Indonesia’s Defense Diplomacy in Advancing ASEAN Agreement on Disaster Management and Emergency Response (AADMER) as a Regulatory Basis for ASEAN First Responder Formation - Ramsi, Oktaheroe; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (International Journal of Humanities, Education, and Social Sciences, 2025)
Southeast Asia ranks among the most disaster-prone regions globally, owing to its complex geological features and tropical climate. In response, ASEAN established the ASEAN Agreement on Disaster Management and Emergency Response (AADMER), the region’s first legally binding framework for disaster management. Despite its significance, AADMER's implementation faces structural limitations, including the principle of non-interference, disparities in member state capacities, and bureaucratic delays that hinder rapid mobilization during the critical "golden time" of disaster response. This study examines Indonesia’s defense diplomacy in reinforcing AADMER as a regulatory basis for developing a regional First Responder mechanism that is timely, coordinated, and effective. Adopting a descriptive qualitative methodology, the research analyzes Indonesia’s engagement through platforms such as the ASEAN Defence Ministers’ Meeting (ADMM) and ADMM-Plus, alongside the roles of key national institutions including the National Disaster Management Authority (BNPB), the Indonesian Armed Forces (TNI), the Ministry of Defense, the Ministry of Foreign Affairs, and cooperation with the ASEAN Coordinating Centre for Humanitarian Assistance (AHA Centre). The findings highlight Indonesia’s strategic role as a country frequently affected by disasters in advancing civil-military interoperability, joint disaster response exercises, and rapid deployment mechanisms under AADMER. Indonesia’s defense diplomacy emerges not only as a tool of traditional security but also as a form of soft power that enhances regional solidarity and institutional legitimacy. The study concludes that Indonesia’s leadership is pivotal in realizing the vision of One ASEAN, One Response through the establishment of a regulation-based, consensus-driven, and collectively operational First Responder system for the region.